The Effect of Environmental Management, Information Technology in the Implementation of Port Sustainability Operations in Ports - Dahlan, Dahlan; Zainal, Veithzal Rivai; Siswanti, Indra; Sugiyono, Sugiyono (International Journal of Entrepreneurship and Business Management, 2024)
This paper attempts to find the right concept to overcome the significant challenges related to environmental quality degradation due to development activities in the port area. Environmental damage, including the impact of port development, has become an increasingly pressing global issue. To face this challenge, countries are trying to integrate sustainability principles through the application of the Port Sustainability concept, with an emphasis on the digitalization of information technology. This approach aims to increase port operational efficiency, minimize excessive use of resources, and ensure environmental sustainability and port operations in the long term.Methodology/approach - research method using Conceptual Framework Development. Where researchers try to analyze the literature on sustainable ports, environmental management, and information technology as key elements in sustainable port operations. The result is a conceptual framework that can be used as a basis for implementing further research. Findings – This research presents a theoretical framework and serves as a basis for further research that will analyze the influence of environmental management on sustainable port operations, the impact of environmental management on information technology development, the relationship between information technology development and the sustainability of port operations, as well as the mediating role of information technology in relation to environmental management and sustainability of port operations The novelty/value of this research concept includes the mediation of information technology in relation to environmental management and the sustainability of port operations, especially port operations, where little research has been carried out.